2020
DOI: 10.1177/0363546520906158
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Femoral Tunnel Placement: An Analysis of the Intended Versus Achieved Position for 221 International High-Volume ACL Surgeons

Abstract: Background: Femoral tunnels that are not anatomically placed within the native anterior cruciate ligament (ACL) footprint during ACL reconstruction are associated with residual instability, graft rupture, and poor clinical outcomes. Although surgeons may intend to place their femoral tunnels within the native ACL attachment, this is not always achieved. This study assesses the variation between intended and achieved femoral tunnel positions in a large cohort of experienced ACL surgeons. Hypothesis: The accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 55 publications
3
25
0
Order By: Relevance
“…Some radiographic studies have revealed that drilling the femoral tunnel through the AM arthroscopy portal rather than using a TT drilling technique resulted in a graft position more posterior and closer to a position that has been suggested as favorable on a lateral radiograph of the knee. 2,26,59,61,66,70,79,84 In the frontal plane, the bone tunnel is inclined more toward the lateral cortex of the lateral femoral condyle when drilled through the AM portal, eventually resulting in superior rotatory stabilization of the knee joint compared with TT drilling. 12 In general, it is difficult to accurately identify the tunnel location on 2dimensional images (radiograph, CT, or MRI) and impossible to accurately measure tunnel diameter (the tunnels appear as ellipses on the axial images).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some radiographic studies have revealed that drilling the femoral tunnel through the AM arthroscopy portal rather than using a TT drilling technique resulted in a graft position more posterior and closer to a position that has been suggested as favorable on a lateral radiograph of the knee. 2,26,59,61,66,70,79,84 In the frontal plane, the bone tunnel is inclined more toward the lateral cortex of the lateral femoral condyle when drilled through the AM portal, eventually resulting in superior rotatory stabilization of the knee joint compared with TT drilling. 12 In general, it is difficult to accurately identify the tunnel location on 2dimensional images (radiograph, CT, or MRI) and impossible to accurately measure tunnel diameter (the tunnels appear as ellipses on the axial images).…”
Section: Discussionmentioning
confidence: 99%
“…30 An AM tunnel is more precise and closer to the anatomic femoral ACL insertion than a TT tunnel, allowing for a more horizontal placement. 59,73 It was recently proposed that vertical and anterior graft placement is required for the TT technique owing to drilling through the tibial tunnel, increasing biomechanical demand during rehabilitation. 58 A vertical graft orientation leads to worse clinical outcomes (pivot shift, KT-1000 arthrometer measurements, and Lysholm score) compared with a more oblique graft placement.…”
Section: Discussionmentioning
confidence: 99%
“…philosophy lies in that it enables an anterior medial or transtibial drilling technique while providing the ability to consistently place the tunnel within the green zone and allows a small amount of latitude in order to support the individuality of the patient's anatomy and notch. However, the achieved tunnel position for transtibial drillers was found to be higher in the intercondylar notch than that for other drilling techniques (outside‐in and AM portal) 26 . In this study, the use of an AM‐portal ACLR technique could initially mark the tunnel position with an electrocautery device and then verify this position by switching to the AM portal.…”
Section: Discussionmentioning
confidence: 80%
“…7,8,17 Studies have demonstrated the difficulty in reproducibility of intraoperative placement of the tibial and femoral tunnels. 18 Therefore, it is important to understand the effect of tunnel placement on graft tension to limit graft excursion. Varady et al completed a computational model to simulate double-bundle reconstruction with various PL tunnel locations and simulated graft fixation at both 0 and 30 degrees.…”
Section: Discussionmentioning
confidence: 99%